Sastra Pariwisata: Lukisan Lanskap dan Rute Wisata Kota Parapat dalam Novel Tepi Tob - Bertova Simanihuruk; Asmyta Surbakti; I Nyoman Darma Putra; Eddy Setia (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
In recent years, a number of literary works, such as poetry, short stories, and novels that describe the tourist attraction of Lake Toba as the background or focus of the story is getting increased. This article aims to describe the landscape and tourist routes of Parapat in Tepi Toba novel by using descriptive qualitative method. Data is collected by close reading, recording, and quoting techniques and analyzed with a literary tourism approach. The results of the analysis show that Tepi Toba novel is not only about tourist’s activities, but also depicts the beauty of the hilly landscape of Parapat intensely and aesthetically filled with tourism supporting facilities and describes travel routes from and to Parapat and tourist travel routes in Parapat. The novelty of this analysis is that Tepi Toba novel has a dual function, namely as a story medium and tourism promotion. This article contributes to providing a new way of looking at the link between literature and tourism promotion.